Determination of Osteocalcin, Bone Alkaline Phosphatase, and Lysyl Oxidase in Iraqi Acromegalic Patients - Abass, Eiman A.; Abed, Baydaa Ahmed; Mohsin, Sohaib N. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
This study was aimed to determine bone formation markers (OST and BALP) and lysyl oxidase in diabetes and non-diabetes Iraqi acromegaly patients in addition to find the relationship among these parameters. The present study conducted 60 acromegalic patients (30 diabetes & 30 non diabetes) attending National Diabetes Center / AL-Mustansiriya University/Baghdad, and 30 healthy individuals as a control group aged (35-60) years. All patients were administrated Sandostatin drug, and they were diagnosed by physician in the hospital.FBG, GH, IGF-1, OST, BALP, and LOX were determined in all groups. The results showed a highly significant rise in all parameters (GH, IGF-1, FBG, OST, BALP, and LOX values in serum of all patients when compared with normal individuals. There were a positive highly significant correlations for lysyl oxidase with osteocalcin and a positive significant with BALP in acromegalic patients. We concluded that lysyl oxidase may be a novel   biomarkers in endocrine diseases like acromegaly.